The Effect of Profitability, Liquidity, and Company Size on Debt Policy in Food and Beverage Companies Listed on the Stock Exchange for the 2018-2022 Period - Reswita, Yefri; Arman, Muhibbul Fikri; Syukri Lukman (ADPEBI, 2024)
This study aims to examine the Influence of Profitability, Liquidity, and Company Size on Debt Policy.Based on the results of the hypothesis testing conducted in this study, it can be concluded that partially profitabilityhas a significant positive effect on debt policy with a calculated t value of 6.326 > t table 1.661 and a significant 0.00 <0.05 so that the H1 hypothesis can be accepted. Liquidity has a significant positive effect on debt policy with a t-valueof 4.455 > t table 1.661 and a significant 0.000 < 0.05 so that the H2 hypothesis can be accepted. The size of the companyhas a positive and significant effect on the debt policy where the value of t is calculated 4.597 > t table 1.661 and is significantby 0.00 < 0.05 so that the H3 hypothesis is accepted. Profitability, Liquidity, and Company Size simultaneously hada positive and significant effect on debt policy with a value of 41.759 > table 2.70 and a significant 0.000 < 0.05 so that the H4hypothesis could be accepted. Therefore, it can be concluded that Profitability (X1), Liquidity (X2), and CompanySize (X3) simultaneously have a positive and significant effect on Debt Policy (Y) obtained the value of the determinationcoefficient written R Square of 0.579, it can be explained that the magnitude of the proportion of the influence ofprofitability, liquidity, and size The company's debt policy was 57.9% while the remaining 42.1% was influenced byother factors outside the variables used in this study.